Irene litanga, a new genus and new species in the Polia generic-complex from China (Lepidoptera, Noctuidae, Hadeninae, Hadenini) - Saldaitis, Aidas; Benedek, Balázs (Zootaxa, 2017)
A new Hadenini genus and species, Irene gen. n. litanga sp. n. (Figs 1–4, 13, 15), are described from China. This is the third paper since 2013 dealing with members of the Polia-complex in the Himalayan region and particularly the mountainous areas of Central China (Saldaitis et al., 2013, 2016). The discovery of a new genus within the Polia genera group again demonstrates the fascinating and surprising diversity of the region. The clarification of the relationship between the genera-subgenera and species belonging to Polia genera group, (e. g. Polia Ochsenheimer, 1816, Kollariana Hacker & Kautt, 1996 [1997], Haderonia Staudinger, 1895, Tricheurois Hampson, 1905, Pachetra Guenée, 1841 and Ctenoceratoda Varga, 1992) remains unclear and disputable, especially in the diverse Himalayan-Sino-Tibetan region. Hopefully our studies will stimulate further exploration and promote the realization of a comprehensive review of this interesting complex.